MANAGEMENT OF PROFESSIONALLY-ORIENTED STUDIES OF INFORMATIVE SUBJECTS FUTURE TEACHERS OF TECHNOLOGY - Sovgira, Svitlana; Chyrva, Hanna; Dushechkina, Nataliia (International Journal of Innovative Technologies in Social Science, 2022)
The article deals with the problem of management of professionally-oriented teaching of Information technology disciplines of future technology teachers. The criteria for the formation of information competence of future technology teachers are identified. Levels of formation of information competence of future technology teachers are characterized: high, medium and low. The methodology of professionally-oriented teaching of Information technology disciplines of future technology teachers is grounded, which includes: content design, integration of traditional and innovative organizational forms and methods, application of active and interactive teaching technologies; their functions, tasks, a set of necessary and sufficient, special professional knowledge and skills that are formed in logically-based process of studying Information technology disciplines. Research-experimental work on the determination of the effectiveness of the method of professionally-oriented teaching information disciplines to future technology teachers was conducted. Quantitative and qualitative analysis of the experimental work to confirm effectiveness of the methodology of professionally-oriented teaching information disciplines to future technology teachers was investigated. The results of the experiment revealed positive dynamics of formation of information competence of future technology teachers (in the experimental groups a high level of formation of information competence increased compared to the establishing stage by 23.85%; medium – by 11.95%, and low one decreased by 35.8%. In the control groups dynamics is insignificant).